Gambaran Pelaksanaan Lima Momen untuk Cuci Tangan di Rumah Sakit Syuhada Haji Kota Blitar - Galuh Nilawati (Journal of Ners and Midwifery, 2016)
Washing hands is a five moments act of hand washing which is done with water or handrub. It is one kind of the infection prevention and as the control of patient safety. The purpose of this study was to determine the implementation of the five moments for hand washing in Syuhada Haji Hospital Blitar City. Method: This was a descriptive research by observation. The population in this study was nurses in the inpatient unit of Syuhada Haji Hospital. The sample was 37 respondents collected by total sampling technique. The data collection was done on March 5 to April 9, 2015. Results: It showed that five moments of hand washing only moments 3 after touching body fluids of patients at risk and 4th moments after touching the patient all the nurses wash their hands with more than 75% nurse hand washing is not appropriate standart operating procedures and the moment the most infrequent hand washing is the moment to-1 before touching the patient. Discussion: This is due to lack of knowledge of nurses about the importance of washing their hands before touching patients can become a bad habit. Recommendations: the researchers were to observe the amount of washing hands nurses in one shift.